Analisis Bioekonomi Sumberdaya Perikanan Tangkap Kabupaten Kepulauan Meranti Provinsi Riau - Syaputra, Eldy; Rifardi, Rifardi; Nasution, Syafruddin (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
This study aims to determine bioekeonomi capture fisheries in the Islands District Meranti (Maximum Sustainable Yield, Maximum Economic Yield, and Open Access), to assess the status of fisheries in the Islands Meranti Regency using models Schaefer, calculating the profitability of fishermen during fishing operations take place. This research was conducted in June - August 2015 in the village of Sungai Gayung Kiri Rangsang Subdistrict, village of Tanjung Kedabu Rangsang Pesisir Subdistrict and village of Telesung Rangsang Pesisir Subdistrict in Meranti Islands Regency. The method used in this research is survey method with interview and observation, while data analysis using bio-economic modeling. The results of this study suggests that the benefits of fishing effort during the arrest operation took place most largely produced from the mackerel and the status of the fishery in Meranti Islands Regency has achieved economic overfishing.